Fine-Tuning Hybrid Deep Learning for Sentiment Analysis of Indonesian Product Reviews - Arwin Halim; Roni Yunis; Erlina Halim (Bina Nusantara University, 2026)
The research aims to build a hybrid deep learning model for sentiment analysis of Indonesian ecommerce product reviews, which represent the expressed opinions of customers. A major challenge in the domain is the presence of non-standard language and highly imbalanced sentiment classes, which hinder accurate classification. Most existing Indonesian sentiment analysis studies rely on relatively small and balanced datasets and primarily use attention mechanisms, an ensemble model, as well as a sequential fusion method. In the research, a large-scale dataset of Indonesian product reviews is collected from the largest e-commerce site in the country. The dataset consists of review text and corresponding product ratings. After preprocessing, semantic features are extracted using a pre-trained Indonesia Bidirectional Encoder Representations from Transformers (IndoBERT) model. The features are then fed into a hybrid model combining Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM) layers through parallel feature-level fusion. Model hyperparameters are optimized using the Tree-Structured Parzen Estimator (TPE), while data imbalance is addressed through resampling methods. Regularization strategies are also applied to mitigate overfitting, and the model is evaluated using stratified k-fold cross-validation. The model hyperparameters are validated using a learning curve, showing a stable and consistent curve following the trend. The results show that the hybrid CNN-LSTM model, combined with Support Vector Machine Synthetic Minority Oversampling Technique (SVMSMOTE), achieves superior performance in distinguishing positive and negative reviews. This outcome reaches Receiver Operating Characteristic - Area Under the Curve (ROC AUC) score of 92.48%, outperforming baseline and conventional machine learning models. These results also show good generalization ability, characterized by consistent values with a very low standard deviation of 0.0009 for each fold.